A subtle alternative splicing event gives rise to a widely expressed human RNase k isoform. - Evangelos D Karousis; Diamantis C Sideris (PLoS ONE)
Subtle alternative splicing leads to the formation of RNA variants lacking or including a small number of nucleotides. To date, the impact of subtle alternative splicing phenomena on protein biosynthesis has been studied in frame-preserving incidents. On the contrary, mRNA isoforms derived from frame-shifting events were poorly studied and generally characterized as non-coding. This work provides evidence for a frame-shifting subtle alternative splicing event which results in the production of a novel protein isoform. We applied a combined molecular approach for the cloning and expression analysis of a human RNase κ transcript (RNase κ-02) which lacks four consecutive bases compared to the previously isolated RNase κ isoform. RNase κ-02 mRNA is expressed in all human cell lines tested end encodes the synthesis of a 134-amino-acid protein by utilizing an alternative initiation codon. The expression of RNase κ-02 in the cytoplasm of human cells was verified by Western blot and immunofluorescence analysis using a specific polyclonal antibody developed on the basis of the amino-acid sequence difference between the two protein isoforms. The results presented here show that subtle changes during mRNA splicing can lead to the expression of significantly altered protein isoforms.